Chemistry, chemical biology and photophysics of certain new chromene–triazole–coumarin triads as fluorescent inhibitors of CDK2 and CDK4 induced cancers. (16th August 2019) - Shankar, E. P. Shyam; Bahulayan, Damodaran
Abstract : The chromene–triazole–coumarin triads synthesized through the MCR-Click strategy possess intense solution state fluorescence, intense solid-state fluorescence and CDK2/CDK4 targeted cytotoxic activity against human cervical cancer cells (HeLa). Abstract : A new series of chromene–triazole–coumarin triads (T1 toT6 ) have been synthesized through the employment of a solvent-free mechanochemical multicomponent reaction, followed by a copper catalyzed (3+2) azide–alkyne cycloaddition (click chemistry). The molecules were investigated for their fluorescence and CDK induced anticancer properties. Half of the molecules (T1, T4, andT5 ) showed fluorescence in the solution state through ICT based electronic transitions, whereas the other half (T2, T3, andT6) showed solid-state fluorescence through aggregation induction. Computational studies on binding affinity revealed that all the molecules are generally selective towards CDK2 and CDK4. The in vitro biological activity studies showed that the moleculesT2 andT5 exhibit potential as fluorescent inhibitors of CDK2/CDK4 induced tumors.T2 andT5 showed an IC50 of 7.5 μg mL −1 and 4 μg mL −1 respectively against the human cervical cancer cell line (HeLa).